Antioxidant and Anti-Proliferative Capacity of a Dichloromethane Extract of Dicerocaryum senecioides Leaves - Mampuru, Leseilane J.; Chokoe, Pirwana K.; Madiga, Maphuti C.; Theron, Annette; Anderson, Ronald; Mokgotho, Matlou P. (IntechOpen, 2012)
None